Effectiveness of Health Education on Improving Knowledge Among Women of Reproductive Age Regarding Early Detection of Cervical Cancer, Sleman - Nur Fadhillah; Cici Rahma Dea; Tika Aprilia; Susar Farasty; Ranny Arsita; Enung Rohimah; Silvia Finida Hannisa; Wedharing Sekar Asmarani; Eka Vicky Yivantina; Fatya Nurul Hanifa (FKM UIN Sumatera Utara Medan, 2026)
Cancer remains a leading cause of morbidity and mortality among women worldwide, with cervical cancer ranking as a major public health problem, particularly in developing countries. Limited knowledge and awareness regarding cervical cancer risk factors and the importance of early detection contribute to low participation of women in cervical cancer screening programs. This community service program aims to increase knowledge and awareness of women of reproductive age regarding early detection of cervical cancer through health education. This activity was carried out on June 4, 2026, in Petung Hamlet, Kepuharjo Village, Cangkringan District, Sleman Regency, Yogyakarta Special Region, using a Community-based health education research approach. A total of 30 participants attended the activity, but only 23 participants completed the pretest and posttest for analysis. Data were analyzed using descriptive statistics and paired sample t-tests. The results showed a significant increase in participants' knowledge, with the mean score increasing from 7.61 ± 1.34 before the intervention to 13.00 ± 1.24 after the intervention (p < 0.001). In conclusion, health education effectively increases knowledge and awareness among women of reproductive age regarding early cervical cancer detection and has the potential to encourage preventive health behaviors and increase participation in cervical cancer screening programs.